2017
DOI: 10.1136/bmjopen-2016-014544
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of second pregnancy among pregnant women: a hospital-based cross-sectional survey in China

Abstract: ObjectivesThis study aimed to explore determinants of second pregnancy and underlying reasons among pregnant Chinese women.DesignThe study was a population-based cross-sectional survey.Setting16 hospitals in 5 provinces of Mainland China were included.ParticipantsA total of 2345 pregnant women aged 18 years or above were surveyed face to face by investigators between June and August 2015.Main outcome measuresThe pregnancy statuses (first or second pregnancy) and reasons for entering second pregnancy.ResultsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In fact, those who had or preferred a son as the first child more often wanted a daughter as their second child. This echoes the findings of Xu et al (2017) who showed that only 2.5% of their participants entered a second pregnancy because of gender preference. Most barriers to childbearing were related to socioeconomic factors.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In fact, those who had or preferred a son as the first child more often wanted a daughter as their second child. This echoes the findings of Xu et al (2017) who showed that only 2.5% of their participants entered a second pregnancy because of gender preference. Most barriers to childbearing were related to socioeconomic factors.…”
Section: Discussionsupporting
confidence: 84%
“…A possible explanation for this might be that infertile women are more aware of their diminished fecundity and related health problems because they were planning for a second child. As expected, this study, which was conducted in gynecology outpatient clinics, reveals a much higher percentage of participants wanting a second child than previous studies conducted in the general public or in general medical practice (Ding and Hesketh, 2006; Xu et al , 2017). Thus, healthcare professionals should be aware of the increased demand for services associated with second pregnancies from this women who are seeking gynecologic care (Cheng and Duan, 2016).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the multivariate analysis for factors that affect smoking among pregnant women, employment status was categorized as non-manual (individual business/civil servants/senior manager and middle-level manager in large and medium enterprise/private entrepreneur/professionals/clerk/students), manual (rural migrant workers/industrial workers of non-agricultural registered permanent residence/business services staff), unemployed, and others [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to note that during 2016, mid-way through the period of data collection for Lotus II, the two-child policy was implemented in China [3]. While initial data on the demographics of women having a second child in China are beginning to emerge [37], it is difficult to assess the impact that this may have had on the study outcomes, if any.…”
Section: Discussionmentioning
confidence: 99%